Digital virtual consumption - Molesworth, Mike; Denegri-Knott, Janice, 1977- (Routledge studies in innovation, organization and technology ;, 2012)
Digital media present opportunities for new types of consumption including desiring, buying, collecting, making, and even selling digital virtual goods. To these activities we can add those taking place in virtual communities of consumption, online shops, brand websites, and online auction houses that together amount to a vast new landscape of consumption. Digital virtual consumption motivates concatenated practices which produce meaningful experience for their users as well as market opportunities to profit from them. Consumers create and maintain elaborate wish lists, engaging with simula.